Cyber Opportunities: Fostering Women's Empowerment through E-Commerce in Afghanistan - Hakimi, Musawer; Fazil, Abdul Wajid; Ahmady, Ezatullah; Qarizada, Abdulkhaliq; Quraishi, Tamana (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
This research undertakes a comprehensive exploration of the intersection between women's empowerment and E-commerce, with a specific focus on the unique challenges and opportunities presented in Afghanistan's post-conflict landscape. Globally, E-commerce has emerged as a transformative force, breaking down traditional barriers and providing avenues for women's active participation in economic activities. However, Afghanistan's socio-cultural context introduces nuanced challenges, including cultural norms, societal expectations, and limited access to technology. Employing a mixed-methods research design, this study gathers insights from 100 Afghan women engaged in E-commerce activities. The findings reveal multifaceted challenges, emphasizing the need for targeted interventions to bridge the digital divide and address cultural barriers. Despite obstacles, the study underscores the resilience of women entrepreneurs in navigating the digital landscape. Education and digital literacy emerge as pivotal factors shaping women's participation, highlighting the necessity for tailored initiatives. The research culminates in key recommendations, advocating for clear national policies, enhanced cybersecurity measures, and digital literacy programs. Support for women entrepreneurship and collaboration with international partners are emphasized to create an inclusive and supportive environment for women in the digital economy. This research serves as a foundational resource for policymakers, researchers, and practitioners, offering actionable insights to empower Afghan women in E-commerce. By implementing the recommended strategies, Afghanistan can pave the way for sustainable development, economic growth, and the meaningful inclusion of women in the digital landscape.